Antidiabetic effects of Melicope lunu-ankenda (Gaertn.) T.G. Hartley on obese STZ-induced diabetic rats using NMR-based metabolomics - Baroor Al-Zuaidy, Mizher Hezam (2016)
In the present study, antioxidant and antidiabetic activities of different Melicope Lunu-ankenda (ML) ethanolic extracts were evaluated using in vitro and in vivo models. Proton nuclear magnetic resonance (1H NMR) and ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) were used to profile the bioactive metabolites in ML leaf extracts. Sixty percent ethanolic ML extract showed the highest inhibitory effect against α-glucosidase, DPPH scavenging activity and ferric reducing antioxidant power. Results based on cell line investigations showed that the leaf extract stimulated the glucose uptake by both 3T3-L1 and HepG2 cells. A discriminatory study on the metabolites responsible for the variation between different ethanolic ML extracts was successfully performed using 1H-NMR-based metabolomics. Principal component analysis (PCA) and partial least square discriminant analysis (PLS-DA) scores revealed clear and distinct separations by PC1 and PC2 with an eigenvalue of 69.9%. The main bioactive compounds found responsible for the separation were isorhamnetin, skimmianine, scopoletin and melicarpinone. The antidiabetic effect was also carried out in vivo using rat models. The extract exerted its effect by decreasing the blood glucose level, insulin resistance, and increasing insulin sensitivity. The treatment of obese diabetic rats with ML extract also resulted in significant decrease in TG, TC, and LDL levels. However, HDL levels were significantly increased. The impact of treatment was also observed in terms of regulation of the renal injury markers and activities of liver enzymes. In addition, NMR-based metabolomics and multivariate data analysis showed clear metabolic differences in the serum and urine samples of healthy, diabetic and treated diabetic Sprague-dawley rats. The metabolomics results demonstrated that the observed metabolic changes were linked with diabetes progression, and metabolic biomarkers were reflected by the perturbed metabolites, hence providing clear understanding regarding the underlying mechanism involved in generation and progression of diabetes. This study presented potent antidiabetic activity of ML and describes its mechanism of action. The NMR based metabolomics approach is supportive for the additional understanding of diabetes-related mechanisms and enhances the metabolic pathways affected in the diabetic rats. These results of the present study may further contribute towards understanding of the underlying molecular mechanism of this medicinal remedy.